1995
DOI: 10.1179/joc.1995.7.6.503
|View full text |Cite
|
Sign up to set email alerts
|

Determination of theIn VitroSusceptibility of 220Mycobacterium fortuitumIsolates to Ten Antimicrobial Agents

Abstract: The authors investigated the in vitro susceptibility to antimicrobial agents of 220 Mycobacterium fortuitum isolates originating from clinical samples (14) of patients attending the Hospital Universitario de Canarias and Hospital del Tórax, and from environmental sources (206): 3 from sea water, 10 from the water supply and 193 from sewage. The Minimum Inhibitory Concentration (MIC) was calculated using the broth microdilution method with Mueller-Hinton Broth without supplement. Amikacin was the most efficacio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is found in natural and processed water sources and known to be responsible for a distinct number of primary infections of the skin, lung, eyes, and soft tissue [2, 57]. …”
Section: Discussionmentioning
confidence: 99%
“…It is found in natural and processed water sources and known to be responsible for a distinct number of primary infections of the skin, lung, eyes, and soft tissue [2, 57]. …”
Section: Discussionmentioning
confidence: 99%
“…This approach may change in future if a single, highly active antimicrobial agent becomes available [ 22 ]. Several antimicrobial agents are active against the RGM [ 2 ]; a recent in vitro antimicrobial susceptibility analysis showed that amikacin [ 23 ], azithromycin [ 24 ], cefoxitine [ 25 ], ciprofloxacin [ 22,25 ], clarithromycin [ 24,25 ], doxycycline [ 25 ], imipenem [ 25 ] and trimethoprim–sulfamethoxazole [ 25 ] remain active against M. fortuitum . Similarly, no in vitro antimicrobial resistance was seen in the mycobacteria isolated from this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Amikacin, a second-line drug for the treatment of M. fortuitum infection, has good bactericidal activity [11,12]; and, interestingly, rifampicin and rifabutin showed good utility when associated with other drugs.…”
mentioning
confidence: 98%